The Semantics of Metaphor - Levin, Samuel R. (Johns Hopkins University Press, 2019)
Originally published in 1977. The Semantics of Metaphor presents a theory for the metaphoric construal of deviant sentences. The theory has two aspects. The first relates to metaphor considered as a productive process of language and describes the mechanisms that operate in its semantic interpretation .This part of the theory is presented in chapters III and IV. The second aspect bears on metaphor considered in the context of poetry and develops a conception of metaphoric truth. This part of the theory is presented in chapters VI and VII. The study is semantic in the sense of dealing with both meaning and truth as these properties pertain to metaphor. Of the remaining chapters, the first isolates certain problems of a pragmatic nature from the central semantic concern, chapter II follows with a survey of recent scholarship on the question of semantic deviance, and chapter V compares the theory expounded in chapters III and IV with three other accounts of metaphor.